An acute presentation of orbital lymphangioma in a five-year-old child in Pakistan - Riaz, Jibran; Amber Mohsin; Saima Ahmad; Fahd Kamal Akhtar (Journal of the Pakistan Medical Association, 2025)
Lymphangiomas are multi-cystic malformations involving the lymphatic and vascular systems. Most commonly occurring in the head and neck region in the paediatric age group, lymphangiomas generally are benign in nature. Given the tumour’s mass, the lymphangioma itself or the accompanying haemorrhage may impair ocular movement and result in compressive optic neuropathy. Furthermore, lymphangiomas have the potential to unevenly infiltrate nearby critical structures including the optic nerve. This trait poses numerous surgical difficulties and makes the therapy of ocular lymphangiomas particularly challenging, especially with the associated haemorrhage. This case report presents an acute case of orbital lymphangioma in a five-year-old child who was treated with monthly sessions of intralesional foam sclerotherapy. Complete resolution of the lesion was observed at the end of the sclerotherapy sessions.